2019
DOI: 10.1158/2159-8290.cd-19-0582
|View full text |Cite
|
Sign up to set email alerts
|

Combination Olaparib and Temozolomide in Relapsed Small-Cell Lung Cancer

Abstract: Small-cell lung cancer (SCLC) is an aggressive malignancy in which inhibitors of PARP have modest single-agent activity. We performed a phase I/II trial of combination olaparib tablets and temozolomide (OT) in patients with previously treated SCLC. We established a recommended phase II dose of olaparib 200 mg orally twice daily with temozolomide 75 mg/m 2 daily, both on days 1 to 7 of a 21-day cycle, and expanded to a total of 50 patients. The confirmed overall response rate was 41.7% (20/48 evaluable); median… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 56 publications
7
149
1
Order By: Relevance
“…Reproducibility across datasets can be tested with CellMinerCDB by plotting the same gene (expression, copy number, or promoter methylation), drug, or microRNA on the x and the y axes. For instance, Schlafen 11 ( SLFN11 ), whose expression is highly predictive of response to a broad range of frontline treatments of SCLC (etoposide, topotecan, cis- and carboplatin) as well as drugs under investigation such as the poly(ADP-ribose polymerase) inhibitors ( Farago et al, 2019 ; Gardner et al, 2017 ; Murai et al, 2019 ; Zoppoli et al, 2012 ) measured by RNA-seq in the UTSW database, shows a 0.92 Pearson correlation with its measured values by Affymetrix microarray in the NCI database ( Figure 2B ). SLFN11 promoter DNA methylation in the NCI database also shows a Pearson correlation of 0.9 with its value in the GDSC ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproducibility across datasets can be tested with CellMinerCDB by plotting the same gene (expression, copy number, or promoter methylation), drug, or microRNA on the x and the y axes. For instance, Schlafen 11 ( SLFN11 ), whose expression is highly predictive of response to a broad range of frontline treatments of SCLC (etoposide, topotecan, cis- and carboplatin) as well as drugs under investigation such as the poly(ADP-ribose polymerase) inhibitors ( Farago et al, 2019 ; Gardner et al, 2017 ; Murai et al, 2019 ; Zoppoli et al, 2012 ) measured by RNA-seq in the UTSW database, shows a 0.92 Pearson correlation with its measured values by Affymetrix microarray in the NCI database ( Figure 2B ). SLFN11 promoter DNA methylation in the NCI database also shows a Pearson correlation of 0.9 with its value in the GDSC ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of SCLC-Global reveals lack of MGMT expression in 33% (N = 38) of the cell lines ( Figure S6D ). Notably, the non-NE SCLC cell lines all express MGMT, indicating that the SCLC-P- and -Y cancer cells are predicted to be poor candidates for TMZ-based therapies ( Farago et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent trial published data, showing the safety and activity of a combination treatment of the PARP inhibitor Olaparib with the DNA damaging alkylating agent temozolomide in patients with relapsed SCLC. The combination was confirmed as safe and active, with an overall response (defined as >30% decrease in the sum of the longest diameter of target legions) in 41.7% of patients and median overall survival of 8.5 months (116). It has also been suggested that a combination of PARP1 inhibitors with immunotherapies may also be an effective combination treatment for lung cancers, particularly in tumors with other DNA repair defects, such as ERCC1 deficiency (117).…”
Section: Parp Inhibitorsmentioning
confidence: 88%
“…NCT03041311 is investing combination carboplatin, etoposide, atezolizumab, and trilaciclib in ES-SCLC. PARP inhibitors have demonstrated, though modest, activity in SCLC patients (83). In addition to combinations with other cytotoxic agents, olaparib is being studied in combination with durvalumab.…”
Section: Other Combination Approaches With Checkpoint Inhibitorsmentioning
confidence: 99%